CIP-PODEROSA CROCANTE, CIP-PODEROSA POLLERA, and CIP-PODEROSA WATIA: New Potato Varieties for Family Farming with Resistance to Late Blight and High Quality for the Frying Industry - Gastelo, M.; Pérez, W.; Eyzaguirre, R.; Quispe, K.; Sanabria, K.; Bastos, C.; Otiniano, R.; Pérez, J.M.; Mendoza, A.; Unda, T.; Andrade-Piedra, J.L. (Springer, 2023)
Three new potato varieties: CIP-PODEROSA CROCANTE, CIP-PODEROSA POLLERA and CIP-PODEROSA WATIA were generated through traditional breeding as healthy and sustainable potato varieties, as compared with popular Peruvian potato varieties INIA 303-CANCHAN and UNICA, to improve living standards of small and medium scale potato producers in Peru and other developing countries. CIP-PODEROSA CROCANTE has high horizontal resistance to late blight (LB), high tuber yield, excellent quality for frying in French fries, red skin, oval tuber shape, cream flesh and superficial eyes, with crispy texture, adapted from 0 to 3700 m above sea level (m.a.s.l.); CIP-PODEROSA POLLERA has high horizontal resistance to LB, yellow skin with blue around the superficial eyes, elongated oval tuber shape, yellow flesh, it is suited to accompany grilled chicken (“Pollo a la brasa”) a typical dish in Peru, adapted from 2000 to 3700 m.a.s.l.; and CIP-PODEROSA WATIA, which in addition to resistance to LB and quality for frying, has excellent aptitude for baking, superficial eyes, light red skin, cream flesh, and is adapted from 0 to 3700 m.a.s.l. These varieties were released in 2022 and officially registered in the national registry of commercial varieties of Peru in 2023. They have low content of glycoalkaloids and acrylamides, require lower use of fungicides, and therefore present higher economic profitability. These varieties can also be used in other countries as parental material in genetic improvement programs or evaluated under regional environments to be registered as new varieties.